Acoustofluidic particle manipulation inside a sessile droplet: four distinct regimes of particle concentration. Issue 4 (12th January 2016) - Destgeer, Ghulam; Cho, Hyunjun; Ha, Byung Hang; Jung, Jin Ho; Park, Jinsoo; Sung, Hyung Jin
Abstract : We have investigated the motion of polystyrene microparticles inside a sessile droplet actuated by surface acoustic waves (SAWs). Four distinct regimes (R1–R4) of particle concentration are identified based on the particle diameters and the SAW frequencies. Abstract : In this study, we have investigated the motion of polystyrene microparticles inside a sessile droplet of water actuated by surface acoustic waves (SAWs), which produce an acoustic streaming flow (ASF) and impart an acoustic radiation force (ARF) on the particles. We have categorized four distinct regimes (R1–R4) of particle aggregation that depend on the particle diameter, the SAW frequency, the acoustic wave field (travelling or standing), the acoustic waves' attenuation length, and the droplet volume. The particles are concentrated at the centre of the droplet in the form of a bead (R1), around the periphery of the droplet in the form of a ring (R2), at the side of the droplet in the form of an isolated island (R3), and close to the centre of the droplet in the form of a smaller ring (R4). The ASF-based drag force, the travelling or standing SAW-based ARF, and the centrifugal force are utilized in various combinations to produce these distinct regimes. For simplicity, we fixed the fluid volume at 5 μL, varied the SAW actuation frequency (10, 20, 80, and 133 MHz), and tested several particle diameters in the range 1–30 μm to explicitly demonstrate the regimes R1–R4. We have further demonstrated the separation of particles (1 and 10 μm, 3 and 5 μm) using mixed regime configurations (R1 and R2, R2 and R4, respectively).